2016
DOI: 10.19044/esj.2016.v12n27p218
|View full text |Cite
|
Sign up to set email alerts
|

Influence Du Poids Maternel Sur L’evolution De La Grossesse Chez Les Gestantes Dans La Ville De Parakou En 2015 Au Benin

Abstract: Introduction:The World Health Organization considers for many years obesity as a pandemic which affects as well the developed countries as the developing ones.The consequences of the overweight on the medical, gynaeco-obstetrical, and surgical plan are no longer demonstrating. Objective:The current paper aims to study the influence of the weight of the mother on the evolution of the pregnancy with the pregnant women in the town of Parakou. Material and methodologicalapproaches: It was about a descriptive trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Similar data have been reported in studies carried out in the United States and Ireland which found similar prevalences of obesity to ours respectively 20% and 25.2% [13] [14]. Already in 2015, a study carried out in Parakou by Achille Awadé Afoukou et al had found a prevalence of obesity and overweight which was respectively 15.8% and 34.9% [7]. In the United Kingdom, a study had reported a prevalence of obesity estimated at 15% [12].…”
Section: Influence Of Excessive Weight Gain On Maternal and Perinatal...supporting
confidence: 89%
See 4 more Smart Citations
“…Similar data have been reported in studies carried out in the United States and Ireland which found similar prevalences of obesity to ours respectively 20% and 25.2% [13] [14]. Already in 2015, a study carried out in Parakou by Achille Awadé Afoukou et al had found a prevalence of obesity and overweight which was respectively 15.8% and 34.9% [7]. In the United Kingdom, a study had reported a prevalence of obesity estimated at 15% [12].…”
Section: Influence Of Excessive Weight Gain On Maternal and Perinatal...supporting
confidence: 89%
“…The dysgravidies such as gestational arterial hypertension, pre-eclampsia are clearly more frequent in obese and overweight women than in pregnant women of normal weight but statistically unrelated [7]. A study carried out in Cotonou found a prevalence of gestational hypertension at 4.7% in obese patients against 1.6% each in patients of normal weight [7]. These results remain lower than ours, and could be explained by the limitation of our analysis only to pregnant women who gained excessive weight during their pregnancy.…”
Section: Maternal and Perinatal Morbidity And Mortalitymentioning
confidence: 99%
See 3 more Smart Citations